3(-1)-5y=10

Simple and best practice solution for 3(-1)-5y=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-1)-5y=10 equation:


Simplifying
3(-1) + -5y = 10

Multiply 3 * -1
-3 + -5y = 10

Solving
-3 + -5y = 10

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -5y = 10 + 3

Combine like terms: -3 + 3 = 0
0 + -5y = 10 + 3
-5y = 10 + 3

Combine like terms: 10 + 3 = 13
-5y = 13

Divide each side by '-5'.
y = -2.6

Simplifying
y = -2.6

See similar equations:

| 6x+13y=-15 | | 7x-35=6x | | 47x-241=3 | | 3(-2)-5y=10 | | 35x-250=10 | | -3x+-22=8 | | 15q+-4r=62 | | 76x*220=3230 | | 2x/48=3:12 | | 878574868x=8384748372929 | | 6/11y=19 | | 2*(1/10) | | .002=1/x | | (3r^5+5r^2-4)-(-7r^5-3r^2+16)= | | F(x)=(3x-7) | | 3c+2d=8 | | 2y-2=3 | | 3x-2+5=2(5x-4) | | z^3-j=0 | | 7.50x+8y=93.50 | | 4x=0.9 | | 6a-4b-2a+24b= | | 6-2(x+8)=6x-26 | | 5(2-7)-y=2(y+1) | | 45+5x=5 | | X+(x-4)+2(x-4)=24 | | y+2.5=.5 | | 5=5x+45 | | 4z+9=-9 | | 7z+8=64 | | 6+18=-y+11 | | 30=q-31 |

Equations solver categories